Methods of State Control of the Electoral Process in the Russian Federation - CHISTOBORODOV, Ilya Grigorievich (Journal of Advanced Research in Law and Economics, 2018)
The article considers the methods of state control of the electoral process in the Russian Federation. The purpose of this article is to consider the concept of the methods of state control of the electoral process. The novelty of the presented article is the description of the applied methods of persuasion, encouragement and coercion. In addition, the author comes to the conclusion that in modern conditions of the development of e-government and e-democracy, the emergence of new methods of control is possible. Electronic technologies will not only affect participants in the electoral process, but also confirm the legitimacy of state authority through the development of democratic institutions. At the same time, they will enable the integration of people into public enterprises for political purposes, will make the methods of influence of subjects of state control more gentle and effective as they allow the impact on the consciousness, will and behavior.